The Relationship between Motivation and Self-Management in Patient with DM in Internist Polyclinic RSUD Kabupaten Tangerang - Aghita Nurprihatini; Annisaa Fitrah Umara; Achmad Badawi (Universitas Muhammadiyah Tangerang, 2020)
Introduction: Diabetes Mellitus (DM) is a disease who characterized by high or low blood glucose values who caused by the inability pancreas to produce insulin, so self-management behavior is very important either for treatment or DM – Related complication preventions, but some DM patient has low motivation to doing self-management. The purpose of this study to was known the relationship between Motivation and Self-Management in Patient with DM in RSUD Kabupaten Tangerang. Methods: The design of this study used analytic observational with a Cross-Sectional approach. Sample taking technique used consecutive sampling with a total sample as much as 74 respondents. The instrument in this study used Treatment Self-Regulation Questionnaires (TSRQ) and the Diabetes Self-Management Questionnaire (DSMQ). Results: The result showed that low motivation with a bad self-management category has 20 respondents (66.7%), while for high motivation with good self-management category has 28 respondents (63.6%). Conclusion: The result of the statistic Chi-Square test showed that the relationship between Motivation with Self-Management in Patients with DM with scoring. Therefore it should be for health providers especially nurse able to increase the motivation of DM patients to do self-management and able to evaluate how the patient's motivation in applying self-management behavior in their life. Keywords: Diabetes Mellitus, Motivation, Self-Management.